2016
DOI: 10.1002/1873-3468.12313
|View full text |Cite
|
Sign up to set email alerts
|

The activation of μ‐opioid receptor potentiates LPS‐induced NF‐kB promoting an inflammatory phenotype in microglia

Abstract: Increased production of proinflammatory cytokines has a prominent role in tolerance to opioids. The objectives of this study were to examine whether μ‐opioid receptor affects proinflammatory signalling through the activation of NF‐kB in microglia. The novelty of the described research is that a low dose of morphine, exerting its effects via the μ‐opioid receptor, increases the DNA‐binding activity of NF‐kB via PKCε, while a high dose of morphine triggers a nonopiate receptor response mediated by TLR4 and, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 50 publications
6
52
1
Order By: Relevance
“…Our results show that biphalin reduced pain-related behavior in a preclinical model of neuropathy in rats, and these analgesic effects seem to be very important from a clinical point of view, especially because preclinical studies have revealed that biphalin has 1000-fold greater analgesic potency than morphine and induces less side effects [17, 18]. Moreover, our results provide strong evidence that biphalin, in contrast to morphine [32, 40, 41], is able to beneficially modulate crucial members of both microglial intracellular signaling pathways and proinflammatory factors, which are known to play a key role in neuropathic pain development.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Our results show that biphalin reduced pain-related behavior in a preclinical model of neuropathy in rats, and these analgesic effects seem to be very important from a clinical point of view, especially because preclinical studies have revealed that biphalin has 1000-fold greater analgesic potency than morphine and induces less side effects [17, 18]. Moreover, our results provide strong evidence that biphalin, in contrast to morphine [32, 40, 41], is able to beneficially modulate crucial members of both microglial intracellular signaling pathways and proinflammatory factors, which are known to play a key role in neuropathic pain development.…”
Section: Discussionmentioning
confidence: 53%
“…Our previous studies have shown that minocycline, an inhibitor of microglial activation [27, 30], strongly delayed the development of morphine tolerance [55, 56] and potentiated MOP, KOP, and NOP ligand analgesia [29, 30]. Several lines of evidence have revealed that morphine increases microglial reactivity [31, 57, 58] and promotes the proinflammatory phenotype of those cells [31, 32, 40]. Moreover, chronic morphine treatment leads to the development of hyperalgesia and allodynia [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, opioids elicit an acute inflammatory response likely via TLR4s [77, 78] and/or MORs [224-226]. There is reliable preclinical [227-229] and non-human primate [223] evidence indicating acute opioid administration is proinflammatory in the periphery and brain.…”
Section: Resultsmentioning
confidence: 99%
“…For example, opioids exert neuroimmune effects via directly binding receptors on microglia, e.g. TLR4s [77, 78] and MORs [224-226]. Other substances, e.g.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%